ClpB chaperone as a promising target for antimicrobial therapy: A narrative review - Sachini J. Udari; Sayoka Shamodhi; Rumesh M. Nelumdeniya; Udayana Ranatunga; Nimesha N. Senadeera; Chathuranga B. Ranaweera (Asian Pacific Journal of Tropical Biomedicine)
The Clp/Hsp100 family, part of the ATPase associated with various cellular activities (AAA+) superfamily, includes caseinolytic peptidase B (ClpB), a highly conserved protein found in bacteria, fungi, protozoa, and plants. Notably, ClpB is present in all ESKAPE pathogens: Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. ClpB plays a crucial role in reactivating and disaggregating proteins, enabling pathogens to survive under host-induced stress and conferring thermotolerance to bacterial cells. Infections caused by ESKAPE pathogens are particularly challenging due to their resistance to broad-spectrum antibiotics and biofilm formation, posing a significant global health threat as they are often multidrug-resistant, extensively drug-resistant, and pan-drug-resistant. Given its absence in human cells and its essential role in bacterial survival under stress, ClpB is a promising target for antimicrobial therapy. Targeting Hsp100 family proteins could lead to the development of novel antifungal and antiprotozoal treatments. This review explores the function of ClpB in the survival of ESKAPE pathogens and the protozoan Plasmodium falciparum. Relevant research findings were compiled using academic databases, and data analysis was performed using Clustal Omega Multiple Sequence Alignment and Boxshade tools.